SUFISM EDUCATION IN THE FORMATION OF MODERATE ISLAMIC ATTITUDES OF YOUTH IN URBAN MUSLIMS - Mustofa, Ali; Hakim, Arif Rahman (AKADEMIKA: Jurnal Pemikiran Islam, 2024)
The purpose of this article is to discuss Sufism education in shaping moderate attitudes. This research discusses new things, namely the formulation of Sufism education for youth, in general Sufism is for the elderly. But it is different from urban Sufism education affiliated with the syadiliyah al mas'udiyah Tarekat. The research method used is qualitative, with data collection methods of interviews. The researcher conducted in-depth interviews with informants related to the Sufism education model for youth and the moderate attitudes that arise in youth. The next method uses observation and documentation, analysis begins with data collection, data condensation, data display, and verification. The results show that the planning of Sufism education begins with setting goals to be achieved (in this case it is in line with the objectives of Sufism education. Sufism Education in the Formation of Moderate Islamic Attitudes of Youth in Urban Muslims. The process of Sufism education in the formation of moderate attitudes of youth is carried out with several stages, namely providing knowledge, implementing knowledge and habituation. Sufism education here is implemented according to its stages. Evaluation of Sufism education in the formation of moderate attitudes of youth is carried out with cognitive and affective, cognitive seeing the educational material that has been memorized, memorizing wirid and practice. While affective is seen from the behavior of Tarekat adherents. The moderate attitude that emerges in santri is that santri have the characteristics of national commitment, tolerance, anti-violence and acceptance of local culture.